Insights from myalgic encephalomyelitis/chronic fatigue syndrome may help unravel the pathogenesis of postacute COVID-19 syndrome. Issue 9 (September 2021) - Komaroff, Anthony L.; Lipkin, W. Ian
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause chronic and acute disease. Postacute sequelae of SARS-CoV-2 infection (PASC) include injury to the lungs, heart, kidneys, and brain that may produce a variety of symptoms. PASC also includes a post–coronavirus disease 2019 (COVID-19) syndrome ('long COVID') with features that can follow other acute infectious diseases and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Here we summarize what is known about the pathogenesis of ME/CFS and of 'acute' COVID-19, and we speculate that the pathogenesis of post – COVID-19 syndrome in some people may be similar to that of ME/CFS. We propose molecular mechanisms that might explain the fatigue and related symptoms in both illnesses, and we suggest a research agenda for both ME/CFS and post–COVID-19 syndrome. Highlights: In some people, the aftermath of acute coronavirus disease 2019 (COVID-19) is a lingering illness with fatigue and cognitive defects, known as post–COVID-19 syndrome or 'long COVID.' Post–COVID-19 syndrome is similar to postinfectious fatigue syndromes triggered by other infectious agents and to myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), a condition that patients often report is preceded by an infectious-like illness. ME/CFS is associated with underlying abnormalities of the central and autonomic nervous systems, immune dysregulation, disordered energy metabolism, and redox imbalance. It is currently unclear if the same abnormalities will be identified in post–COVID-19 syndrome. The USA and other developed nations have committed considerable support for research on post–COVID-19 illnesses.